(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2017)
The aim of the present work was to prepare and evaluate fast dissolving tablets of nebivolol with a view to enhance patient compliance and minimize the side effects. In this study, fast dissolving tablets of nebivolol were formulated by direct compression method using mucilages of tapioca seeds (Manihot esculenta), basella climb (Basella alba), red sorrel (Hibiscus sabdariffa) as natural disintegrants and crosspovidone as a synthetic superdisintegrant in different ratios with directly compressible mannitol (Pearlitol SD 200) as a diluent to enhance the mouth feel. The prepared formulations were evaluated for hardness, friability, drug content, in vitro dispersion time, wetting time, water absorption ratio, in vitro drug release, stability and excipients interaction. Among all the formulations, the formulation (FHD3) containing 8% w/w mucilage of Hibiscus sabdariffa was the overall best formulation (t50% 1.7 min) based on in vitro drug release studies. Stability studies on the formulations indicated that there are no significant changes in drug content and in vitro dispersion time (p<0.05). From the above studies, it can be concluded that fast dissolving tablets of nebivolol can be prepared using different mucilages as natural disintegrants for faster dispersion and disintegration in the mouth. Dhaka Univ. J. Pharm. Sci. 15(2): 143-149, 2016 (December)